Economic growth in Latin America: Structural breaks or fundamentals? - Rómulo A. Chumacero; J. Rodrigo Fuentes (Estudios de Economía, 2006)
Despite having accumulated physical and human capital at significant rates, Latin America's growth has been generally disappointing. Successful growth episodes have been accompanied by surges in TFP, sound and stable macroeconomic policies, and fewer distortions and government interventions. Structural breaks are often cited as sources of the disappointing and heterogeneous growth performance of countries in Latin America. We find that, once controlled for external shocks and a measure of distortions, the behavior of per capita GDP in a sample of Latin American countries is remarkably stable.
Keywords: O47; C32; 330; growth; Latin America; structural breaks